Tiger girls : women and enterprises in the People's Republic of China - Chen, Minglu (Abingdon, Oxon : Routledge, 2011)
'The last three decades of the People's Republic of China has been characterized by decentralization, marketization and privatization. What might be expected from a developing country like China with a significant number of women in the labour force? Do the traditional values of male superiority still stay the same in the background of China's great social change? The notion of'tiger girls' seems to reflect one of the alternative paths that is now becoming available to the modern Chinese woman. The social development and changes in recent China have provided women with access to education, employment, and independent income. Consequently, they are casting off obedient and subordinate roles and gaining more and more individual power and strength outside the home. Using empirical research findings from three localities in China, Tiger Girls examines the deeper realities of women entrepreneurs in China, and by extension the role of leading women in the workforce'--
Includes bibliographical references and index.
Keywords: Businesswomen -- China; Women -- China; Social change -- China